Resource use content online learning: YouTube - Martha Claudia Rodríguez Villalobos; Jessica Fernández Garza (Apertura, 2017)
The article demonstrates the results of implementing the use of online learning contents found on the resource YouTube in the statistics course of graduate level. The objective was to verify whether the use of the educational YouTube channel tool promotes better results in students learning Mastery in Business Administration from the Tecnologico de Monterrey in the quarter of April to July 2016. The method consisted of sharing weekly videos with the students that farther exemplify the materials related to the subject matter for a more comprehensive understanding of these concepts. The research was conducted by descriptive and inferential statistics dividing students into a control or experimental group. After analysis, it was found that from second partial exam and on the group that had access and exposure to the shared videos on the educational channel on YouTube had better grades than those without such tool, so it is concluded that there is a benefit in academic achievement by using this resource for learning content.